Rethinking the incentive system in science: animal study registries: Preregistering experiments using animals could greatly improve transparency and reliability of biomedical studies and improve animal welfare. (23rd December 2019) - Heinl, Céline; Chmielewska, Justyna; Olevska, Anastasia; Grune, Barbara; Schönfelder, Gilbert; Bert, Bettina
Abstract : The Animal Study Registry offers scientists a range of benefits by preregistering their studies. Wider adoption could address the reproducibility problem in biomedical research and enhance animal welfare.